Synergetic Learning Model: The Sum is Greater - Thompson, Kevin S. (International Journal of Advanced Corporate Learning (iJAC), 2020)
Instructional design models provide process insight that guides learning solution designers in their work to meet learning objectives and improve performance. Human resource development scholars often focus on individual learning components that support meeting learning and performance objectives. Learning practitioners who design learning solutions must review significant amounts of research studies to extract information that may assist them in their roles. This paper introduces the evidence-based Synergetic Learning Model, focused exclusively on design, intended to leverage the work of scholars holistically for the benefit of learning practitioners.